Faktor-Faktor yang Mempengaruhi Burnout pada Wanita Bekerja di Kabupaten Banyumas - Swasti, Keksi Girindra; Ekowati, Wahyu; Rahmawati, Eni (Jurusan Keperawatan FIKES UNSOED, 2017)
The globalization era has given many changes in some aspects of life such as women participation in work field. There are women can perform their potential ability in doing their work. The effects of doing their role, women oftentimes feel weary not only physical but also mental and emotional therefore it can influence their work performance and personal life. This condition is called by Ã¢â‚¬Å“burnoutÃ¢â‚¬Â. Burnout is influenced by individual, environment and cultural factor. Based on that problem, the researcher is interested to find out some factors that influence burnout for working women in Banyumas Regency. This research is quantitative by descriptive analysis design and the sample is chosen by simple random sampling. The relationship between characteristic of respondent demography and burn out was analyzed by Chi-Square and Sommers d test. The result of analysis are 55% respond are mild burnout and 42,5% are moderate burnout. Level of education, kind of work, amount of income and work duration are some factors that influence burnout for working women in Banyumas Regency. Based on that fact, it is needed some efforts to prevent sustainable burnout.